Metodyczne aspekty oceny efektywności działalności przedsiębiorstwa rolniczego - Franc, Justyna (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2001)
In the paper there were presented two tools for assessing any firm's performance: Du Pont method and the method of four elements. The first method allows an evaluating the influence of factors determining the effectiveness of assets and own funds of the firm. The second one is used for assessing the financial results of the firm. Methods under consideration can be applied as supplementary for basic tools of financial analysis in the organisation. Although they also are the useful tools for helping management make decision, there are some weaknesses that should be noted. In addition, the analysis is only as good as the level of general knowledge about the investigated organisations (enterprises).